2017
DOI: 10.1155/2017/9536869
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Cesarean Scar Ectopic Pregnancy Treated with Systemic Methotrexate

Abstract: Cesarean scar pregnancy (CSP) is a rare event; however its incidence has been rising due to the increasing rates of cesarean deliveries. The majority of cases present with signs or symptoms requiring surgery, which often results in hysterectomy. The recurrence of CSP is even rarer with only few cases which have been reported. This is a report of recurrent cesarean scar ectopic pregnancy (RCSP) that was promptly diagnosed and managed with only systemic methotrexate. This was a 30-year-old woman, with a history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This is extremely rare. Only few cases have been described in the literature (21)(22)(23). Unfortunately, no information regarding her treatment during this episode is available.…”
Section: Resultsmentioning
confidence: 99%
“…This is extremely rare. Only few cases have been described in the literature (21)(22)(23). Unfortunately, no information regarding her treatment during this episode is available.…”
Section: Resultsmentioning
confidence: 99%
“…There is little scientific data on the risk of recurrence of the condition in future pregnancy, the role of the interval between the previous caesarean delivery and re-occurrence of caesarean scar pregnancy [7,46]. Few published studies have reported on the low risks or recurrence of SCP, suggesting that implantation into the CS scar is more likely a chance event, than the result of an affinity of a pregnancy for implanting into the scar [47].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our data show that, among women with a prior CSP, the recurrence rate is higher than previously suspected based upon mostly single‐case reports or series with few cases 5,23–25 . This information should be incorporated into the initial counseling of women presenting with CSP, regardless of their future obstetric plans, in order that they understand realistically the outcome of any future pregnancy.…”
Section: Discussionmentioning
confidence: 65%
“…Based on these 17 studies, there were 1743 diagnoses of CSP. Sixteen of these studies (including 1643 diagnoses We found a further four articles reporting single, recurrent CSP cases 5,[23][24][25] , but these were not included in Table 3 due to a lack of pertinent data which made it impossible to include them in the statistical analysis.…”
Section: Resultsmentioning
confidence: 99%